HIV-ASSOCIATED NON HODGKIN LYMPHOMA: A CASE SERIES STUDY FROM TURKEY - Somay, Kayra; Çöpür, Sidar; Osmanbaşoğlu, Emre; Masyan, Helin; Arslan, Harun; Akay, Olga Meltem; Tekin, Süda; Ferhanoğlu, Burhan (African Journal of Infectious Diseases (AJID), 2020)
Background: Human immunodeficiency virus (HIV) is a global health concern with major risks for opportunistic infections and predisposition to malignancies including Kaposi sarcoma associated with Human Herpes Virus-8 (HHV-8) and non-Hodgkin lymphoma (NHL) commonly associated with Epstein Barr Virus (EBV). Although the exact mechanisms of predisposition to certain malignancies are unclear, HIV (+) cancer patients typically have poorer prognosis. Materials and Methods: We included all five HIV positive NHL patients receiving antiretroviral therapy (ART) and chemotherapy in our clinic and aim to determine their follow-up outcomes associated with ART. Results: The use of ART in conjunction with chemotherapy regimens lead to better therapeutic outcome in our cases with no mortality over three years of follow-up despite high rates of poor prognostic factors and studies demonstrating 1-year survival rates of approximately 30% in HIV-associated lymphoma. No significant adverse effect has been recorded. Conclusion: We recommend use of ART along with chemotherapy regimens in HIV positive lymphoma patients for better treatment response.